Screening Rice Germplasm against Sheath Blight Disease of Rice and its Integrated Management in Bangladesh - Parveen, S; Ali, MA; Ali, MA (Bangladesh Rice Journal, 2019)
Fifty-seven rice germplasm collected from BRRI Genebank were screened against sheath blight (ShB) by artificial inoculation in field and laboratory conditions in T. Aman 2012. Significant differences on relation to lesion height (RLH) among the germplasm were observed, where the highest (83%) was recorded in susceptible check, BR11 and the lowest (8.33%) was in Orgoja. Severity score of ShB was recorded maximum (9) in Dudhsail, Basi, Chaula mari, Holdemota, Calendamota, Semmua, Kotijira, Halisail, Horakani, Kalisura, Ashfuli, Huglapata and BR11 as highly susceptible to ShB, whereas it was minimum (1) in Orgoja. Gopal ghosh was observed as moderately tolerant with 27.33% RLH and severity score 3, while Kala binni, Khazur chari, Binni, Kalagora, Patjait and Dorkumur found moderately tolerant with severity score 5. In detached sheath inoculation method in test tube, most of the germplasms found highly susceptible, except Orgoja as resistant and Gopal ghosh as moderately tolerant. However, Orgoja showed resistance in both field inoculation and detached sheath inoculation methods. But, Dorkumur was found moderately tolerant in field and highly susceptible in detached sheath inoculation in laboratory. The experiment of Integrated Disease Management (IDM) packages was conducted in the farmer’s field with BR11 at Fulpur, Mymensingh during T. Aman 2013. The IDM practices of rice ShB resulted profound effect. Relative lesion height, percent disease index, tiller infection and hill infection were maximum (68%, 69%, 86% and 79% respectively) in T6 (control) and minimum in T1 [FDR (removal of floating debris) + 30 July transplanting + Potash (K) fertilizer (202 g decimal-1) + Top dressing of urea (247 kg ha-1) in four equal splits at 15 days interval + single spray of fungicides of Azoxystrobin 10% (0.17 kg ha-1) + Tebuconazole 90% (500 ml ha-1)]. Moreover, the highest number of panicles per m2, filled grains per panicle and grains yield were recorded in T1 (160, 150 and 6.25 t ha-1 respectively) and the minimum in T6 (227, 120 and 3.6 t ha-1 respectively). Therefore, the best IDM package was T1 for its effective control of ShB disease as well as yield maximization of rice. Finally, Orgoja could be used in resistance breeding for varietal improvement and the IDM package of T1 need to be recommended to prescribe in the farmer’s field after simulation in different AEZs and seasons with different varieties of Bangladesh. Bangladesh Rice j. 2018, 22(2): 1-12